STRATEGI UMKM DALAM MENINGKATKAN PARIWISATA DENGAN MODEL EDUPAKS DI PEMERINTAH KALIMANTAN TENGAH - Latifah, Eny; Abdullah, Rudi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
The aim of this research is to determine the strategy of MSMEs in increasing tourism using the EDUPAKS model in the Central Kalimantan Government. The research method is descriptive qualitative type of literature study. The results of the research are that the EDUPAKS concept is a combination of artificial tourism innovation by providing education on product processing using palm oil and presenting KAMI to provide education on the importance of sharing. The strategy that can be used in the MSME sector in tourism development in Central Kalimantan is to carry out: product innovation, using hybrid marketing, QRIS (Modern payment products) and KAMI (Mini Cans). How to realize Palm Oil Tourism Education (EDUPAKS) in an effort to increase the number of tourists in Central Kalimantan by establishing a mutualistic symbiosis of the MSME sector as material managers and the Tourism sector as providers of EDUPAKS and KAMI